The ability of abdominal ultrasound to identify gastrointestinal foreign body characteristics prior to attempted laparoscopic-assisted gastrointestinal foreign body removal. - Toth, Darby (My University, 2025)
Objective: To determine the accuracy of abdominal ultrasound (AUS) in determining gastrointestinal foreign body obstruction (GIFB) type, location, size and shape; and to determine the success rate of laparoscopic-assisted GIFB removal (LGFBR) with GIFB of various sizes, shapes, and locations. Study Design: Prospective clinical study. Animals: Client-owned dogs (30) that underwent LGFBR (31). Methods: Dogs with known or suspected GIFB obstruction underwent a preoperative AUS performed by a board-certified radiologist. GIFB type, location within the gastrointestinal tract, size, and shape were recorded, as well as the presence or absence of peritoneal fluid, pneumoperitoneum, or gastrointestinal mural changes. LGFBR was then attempted in all patients. Surgical findings were compared to preoperative ultrasound findings. Results: AUS was able to determine the type, location, and shape of GIFB with accuracies of 96.8%, 74.2%, and 93.5% respectively. AUS had moderate accuracy (80%), at identifying the presence of adhesions, and was inaccurate at determining GIFB size. LGFBR was successful in 16/30 (53.3%) of cases, including 2/7 (28.6%) of linear, 14/23 (60.9%) non-linear, and 1/1 (100%) gastric foreign bodies, but was not successful for GIFB near the caudal duodenal flexure (0/2, 0%). Conclusion: Preoperative AUS is a useful diagnostic to aid in determining the suitability of a patient to undergo LGFBR. Linear and gastric foreign bodies were not contraindications to LGFBR, however GIFB located at the caudal duodenal flexure were. Clinical Significance: Based on our study, AUS would be recommended prior to attempting LGFBR. Further studies are recommended to investigate contraindications to LGFBR.
Keywords: Laparoscopic-assisted gastrointestinal foreign body removal; Gastrointestinal foreign body; Abdominal ultrasound; Minimally invasive surgery; Patient selection